A state-of-the-art on development of geopolymer concrete and its field applications. (June 2022) - T., Srividya; P.R., Kannan Rajkumar; M., Sivasakthi; A., Sujitha; R., Jeyalakshmi
Abstract: Massive growth in the infrastructure industry and development has led to a phenomenal increase in cement usage. The cement industry emits the greenhouse gas (CO2 ) and cement production requires more embodied energy. There is an increasing research interest in geopolymers (GP) for developing an alternate binder for civil engineering applications because of its low energy consumption and eco-friendly nature. GP contain alkali-activated material, which is relatively new, and Geopolymer concrete (GPC) has superior mechanical and durability properties compared to ordinary Portland cement (OPC) concrete. The objective of the review article is to make all-encompassing review of long-term (LT) and short-term (ST) properties of GP, their chemistry, reaction mechanism, effect of reaction parameters, fresh properties, stability under elevated temperature exposure, bond between steel and reinforcement and various field implementations. It is concluded that GPC can achieve structural grade strength when different industrial waste materials as precursors are used in its preparation by varying the alkaline concentration, curing method and curing temperature. It is also concluded that GP gives better thermal resistance at elevated temperature exposure up to 1000 °C whereas OPC fails. Various research and development works carried out in India by utilising the locally available industrial waste-based source materials are also discussed. Applications of GP technology in current scenario have also been reviewed. The gap in GP technology pertaining to corrosion, carbonation and leaching effects of GPC need to be focussed in future research. Highlights: Geopolymers are semicrystalline or amorphous alumino-silicate polymeric network structures. The chemistry and reaction mechanism of geopolymers are discussed along with their synthesis. Geopolymer concrete possesses equivalent or superior properties than ordinary Portland cement concrete. Various research and field applications of GP concrete around the world are discussed